A Survey on Helminth Parasites of Fishes from Jaikwadi Dam, Maharashtra State of India - D.S.2, and Nale V.B.3, Nimbalkar R.K.1*, Shinde S.S.2, Tawar (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial; mso-ansi-language: EN-US;">Ninety samples of Clarias batrachus (n=20), Heteropneustes fossilis (n=22), Tilapia mossambica (n=28) and Wallago attu (n=20) was caught in Jaikawadi Dam of Paithan Thasil of Aurangabad District in December and January 2010, all of them are carnivorous fishes commonly available in Jaikwadi dam. Nine helminth species including three cestodes (Bothriocephalus acheilognathi, Polyonchobothrium clarias and Proteocephalus glanduliger), four nematodes (Paracamallanus cyathopharynx, Capillaria, Contracaecum sp. larvae and Eustrongylides sp. larvae), out of two trematodes, one was digenean (Glossidium pedalum) and other was acanthocephala (Acanthogyrus) were found in Clarias batrachus, Tilapia mossambica, Heteropneustes fossilis, Wallago attu.